2019
DOI: 10.1111/hex.12915
|View full text |Cite
|
Sign up to set email alerts
|

Researchers' perspectives on public involvement in health research in Singapore: The argument for a community‐based approach

Abstract: Background Singapore is becoming a world‐class research hub, promoting the advancement of patient care through translational clinical research. Despite growing evidence internationally of the positive impact of public involvement (PPI), in Singapore PPI remains unusual beyond patient participation as subjects in studies. Objective To explore health researchers' understandings of the principles, role and scope of PPI, and to identify barriers and opportunities for implementation in Singapore. Design Semi‐struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(68 citation statements)
references
References 55 publications
1
67
0
Order By: Relevance
“…Similarly, our A scale provides an opportunity for clinicians to enhance patient care by detecting and address-ing easily correctable erroneous beliefs, especially as the expertise and authority of health professionals are highly respected in Singapore's hierarchical culture. 44 We found that higher K and A scores were associated with greater likelihood of reporting no difficulty accessing DR-related information, a proxy measure of patients' DR-related health literacy. 45 This is important, as limited health literacy has been independently associated with worse glycemic control and higher rates of DR. 47 This suggests that improving DR-related K and A could also enhance DR-specific health literacy, which, in turn, may improve clinical outcomes for people with diabetes and DR. Other studies have also reported a relationship between K and A and DR-related practices in patients with DME and DR, such as getting an eye exam, 15,16 although we were not able to assess this relationship in our study.…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, our A scale provides an opportunity for clinicians to enhance patient care by detecting and address-ing easily correctable erroneous beliefs, especially as the expertise and authority of health professionals are highly respected in Singapore's hierarchical culture. 44 We found that higher K and A scores were associated with greater likelihood of reporting no difficulty accessing DR-related information, a proxy measure of patients' DR-related health literacy. 45 This is important, as limited health literacy has been independently associated with worse glycemic control and higher rates of DR. 47 This suggests that improving DR-related K and A could also enhance DR-specific health literacy, which, in turn, may improve clinical outcomes for people with diabetes and DR. Other studies have also reported a relationship between K and A and DR-related practices in patients with DME and DR, such as getting an eye exam, 15,16 although we were not able to assess this relationship in our study.…”
Section: Discussionmentioning
confidence: 68%
“…Effective and e cient use of resources PPI is often characterised as a time and energy intensive activity, and it can be this that deters researchers' enthusiasm and engagement for PPI 6 . The "PPI Hawker" addresses some of these concerns as it does not require the administrative burden or the expenses of sending out invitations, hiring a venue or transport for participants.…”
Section: Ppi Facilitator's Experiencementioning
confidence: 99%
“…Patient and public involvement (PPI) in research is de ned as research that is carried out 'with' or 'by' members of the public rather than 'to', 'about' or 'for' them. Although PPI is a common component of health research in Western countries, such as the UK, Australia and Canada [1][2][3][4][5] , PPI is still in an early stage of development in Asian countries, including Singapore 6 . It is recognised that PPI enhances the quality and relevance of the research, and its impacts are greater when implemented early in the research cycle [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Effective and efficient use of resources PPI is often characterised as a time and energy intensive activity, and it can be this that deters researchers' enthusiasm and engagement for PPI [6]. The "PPI Hawker" addresses some of these concerns as it does not require the administrative burden or the expenses of sending out invitations, hiring a venue or transport for participants.…”
Section: Ppi Facilitator's Experiencementioning
confidence: 99%
“…Patient and public involvement (PPI) in research is defined as research that is carried out 'with' or 'by' members of the public rather than 'to', 'about' or 'for' them. Although PPI is a common component of health research in Western countries, such as the UK, Australia and Canada [1][2][3][4][5], PPI is still in an early stage of development in Asian countries, including Singapore [6]. It is recognised that PPI enhances the quality and relevance of the research, and its impacts are greater when implemented early in the research cycle [7][8][9].…”
Section: Introductionmentioning
confidence: 99%